Attitudes and opinions of the abattoir sector toward the control and prevention of microbiological foodborne pathogens. Issue 5 (23rd May 2019) - Wijnen, Lena I.; Biasino, Wauter; Verbeke, Wim; De Zutter, Lieven; Seliwiorstow, Tomasz; Van Damme, Inge
Abstract: The abattoir sector plays a crucial role in controlling foodborne hazards, so insight in the incentives that motivate abattoirs to implement control measures is of great relevance to food safety risk managers and policy makers. Therefore, a cross‐sectional telephone survey was conducted to assess the attitudes and opinions of abattoirs in Belgium and the Netherlands toward preventive measures for controlling microbiological pathogens. A total of 80 abattoirs participated, generally they seem to be aware of the most hazardous bacterial pathogens for public health and of their responsibility and potential role to control these hazards. However, significant differences were observed between animal species, company size, and countries. Practical applications: The findings of this survey may help to specify and adjust the set‐up and implementation of control strategies and measures to the diverse incentives and opinions of different food business operators.